Ciliates in man-made mountain reservoirs - Sommer, Fabian; Sonntag, Bettina; Rastl, Nikolai; Summerer, Monika; Tartarotti, Barbara (Frontiers in Environmental Science, 2022)
Climate warming has multiple effects on an environment. Especially the Alpine region is affected by changing conditions, which do not only have ecological but also economic impacts in respect to winter sports tourism. Due to higher environmental temperatures and less precipitation, artificial snow making is becoming increasingly important and consequently, mountain reservoirs for water storage are built. In these systems, planktonic communities are not only influenced by the naturally harsh environmental conditions of the alpine region, but also by severe changes in water level fluctuations due to water withdrawal and re-filling within short time periods. Information on planktonic communities and species traits in such man-made water bodies is nonexistent. Here, we focused on ciliates, a group of unicellular protists known to adapt and respond rapidly to changing environmental conditions. Simultaneously, we identified abiotic and other biotic factors that shaped these microbial communities. We investigated the species composition, abundance and species traits of ciliates in eleven mountain reservoirs in the Tyrolean Alps, Austria, and hypothesized that these communities differed significantly from natural ones. The mountain reservoirs were investigated twice during the ice-free season and water chemistry, chlorophyll a, bacteria, zooplankton, and ciliates were sampled. We detected 48 ciliate taxa in total, with an average of five taxa per mountain reservoir. A wide range of abundance (summer: 24 to >15,600 Ind L-1; autumn: 38 to ~7,500 Ind L-1) and no clear pattern in the community composition was found, most likely due to water level fluctuations and the source of water used for filling the mountain reservoirs. The ciliate abundance was significantly affected by pH, nutrients, but also water transparency and potential predators (crustaceans). Planktonic ciliates dominated the mountain reservoirs and, surprisingly, mixotrophic species, typically found in natural (alpine) lakes, were only rarely observed. Our data suggest that in these fast-changing systems, local factors seem to be more important than regional ones.